Analysis of the Concept of Educational Financing Management and its Implementation to Improve the Quality of Education - Khairan, Ihsan; Karim , Hamdi Abdul (Journal of Loomingulisus ja Innovatsioon, 2024)
This study aims to analyze the basic concepts of education financing and its implications for improving the quality of education. This research uses the Library Research method. The results showed that improving the quality of an educational institution / institution is the hope and desire of the community who use educational services. Therefore, to make this happen, various strategic efforts have been made by the government and the community as managers and education stakeholders. Among them, what the government is doing is designing national education standards. Based on the law national education system Number. 20 of 2003 there are 8 national standards, which aim to improve the quality of an educational institution. Based on government regulations, one of the eight national education standards is a financing standard. Education financing is the most important and inseparable thing in education management activities. So, among other things, the government policy is to roll out BOS funds at the school level If it is accountable, it will increase the credibility of the educational institution. If it is credible, it will automatically improve the quality of the educational institution.